Optimizer Smart System for the treatment of chronic heart failure: Overview of its safety and efficacy. (3rd June 2021) - Chera, Habib Hymie; Al-Sadawi, Mohammed; Michelakis, Nickolaos; Spinelli, Michael
ABSTRACT: Introduction : Heart failure (HF) is a major cause of morbidity and mortality throughout the world. Despite the significant progress in the prevention and treatment of HF, mortality rates still remain high. Device therapy for HF includes cardiac resynchronization therapy (CRT) and the use of an implantable cardioverter-defibrillator (ICD). Recently, a new device therapy for the treatment of HF became available, called cardiac contractility modulation (CCM). CCM is a new device therapy for patients with HF who do not qualify for CRT. It is implanted in a minimally invasive manner to improve the patient's morbidity. Optimizer Smart System is a new device that delivers CCM therapy. Areas covered : We review the function of the Optimizer Smart System, the data from the recent clinical trials, and discuss its efficacy and future projections in the treatment for HF. Expert opinion : CCM therapy provided with the Optimizer® Smart System is safe, feasible, and applicable to a wide range of patients with HF. To demonstrate the effectiveness of the Optimizer Smart System's use merits further large multicenter randomized controlled trials.